Matrix mKdV Integrable Hierarchies via Two Identical Group Reductions - Wen-Xiu Ma (Mathematics)
This paper applies a pair of identical group reductions or similarity transformations to formulate integrable models. An application to the Ablowitz–Kaup–Newell–Segur (AKNS) matrix spectral problems leads to reduced matrix modified Korteweg–de Vries (mKdV) integrable hierarchies. In particular, several illustrative examples of reduced matrix mKdV integrable models are derived from the reduced AKNS matrix spectral problems.